An on-line SPE-HPLC method for effective sample preconcentration and determination of fenoxycarb and cis, trans-permethrin in surface waters - Šatínský, Dalibor; Naibrtová, Linda; Fernández-Ramos, Carolina; Solich, Petr (Talanta, 2015)
A new on-line SPE-HPLC method using fused-core columns for on-line solid phase extraction and large volume sample injection for increasing the sensitivity of detection was developed for the determination of insecticides fenoxycarb and cis-, trans-permethrin in surface waters. The separation was carried out on fused-core column Phenyl-Hexyl (100×4.6 mm), particle size 2.7 µm with mobile phase acetonitrile:water in gradient mode at flow rate 1.0 mL min(-1), column temperature 45°C. Large volume sample injection (1500 µL) to the extraction dimension using short precolumn Ascentis Express RP C-18 (5×4.6 mm); fused-core particle size 2.7 µm allowed effective sample preconcentration and efficient ballast sample matrix removal. The washing mobile phase consisting of a mixture of acetonitrile:water; 30:70, (v/v) was pumped at flow rate of 0.5 mL min(-1) through the extraction precolumn to the waste. Time of the valve switch for transferring the preconcentrated sample zone from the extraction to the separation column was set at 3rd min. Elution of preconcentrated insecticides from the extraction precolumn and separation on the analytical column was performed in gradient mode. Linear gradient elution started from 40% of acetonitrile at time of valve switch from SPE column (3rd min) to 95% of acetonitrile at 7th min. Synthetic dye sudan I was chosen as an internal standard. UV detection at wavelength 225 nm was used and the method reached the limits of detection (LOD) at ng mL(-1) levels for both insecticides. The method showing on-line sample pretreatment and preconcentration with highly sensitive determination of insecticides was applied for monitoring of fenoxycarb and both permethrin isomers in different surface water samples in Czech Republic. The time of whole analysis including on-line extraction, interferences removal, chromatography separation and system equilibration was less than 8 min.
Keywords: chemické látky znečišťující vodu; Environmental Monitoring; Permethrin; monitorování životního prostředí; Lakes; vysokoúčinná kapalinová chromatografie; Česká republika; řeky; insekticidy; Phenylcarbamates; Water Pollutants, Chemical; on-line systémy; Rivers; jezera; Chromatography, High Pressure Liquid; Czech Republic; extrakce na pevné fázi; permethrin; Insecticides; Online Systems; fenylkarbamáty; Solid Phase Extraction